2020
DOI: 10.5194/gmd-13-249-2020
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent kinetic energy over large offshore wind farms observed and simulated by the mesoscale model WRF (3.8.1)

Abstract: Abstract. Wind farms affect local weather and microclimates; hence, parameterizations of their effects have been developed for numerical weather prediction models. While most wind farm parameterizations (WFPs) include drag effects of wind farms, models differ on whether or not an additional turbulent kinetic energy (TKE) source should be included in these parameterizations to simulate the impact of wind farms on the boundary layer. Therefore, we use aircraft measurements above large offshore wind farms in stab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 42 publications
1
52
1
Order By: Relevance
“…This result disagrees with the findings by Grashorn and Stanev (2016) and Rivier et al (2016), who reported increased turbidity caused by OWF foundations. Lampert et al (2020) provide airborne observations of a large-scale regional reduction in wind stress downwind of the OWF in the German Bight, confirming results of previous studies (e.g., Djath et al, 2018;Djath and Schulz-Stellenfleth, 2019;Cañadillas et al, 2020;Siedersleben et al, 2020). Consistent with the observations by Lampert et al (2020), atmospheric model simulations by Siedersleben (2019) show a reduction of wind speed by 5%-25% inside the wind wake 5 km downwind of a wind farm.…”
Section: Effects Of Wind Turbines On the Wind Fieldsupporting
confidence: 87%
“…This result disagrees with the findings by Grashorn and Stanev (2016) and Rivier et al (2016), who reported increased turbidity caused by OWF foundations. Lampert et al (2020) provide airborne observations of a large-scale regional reduction in wind stress downwind of the OWF in the German Bight, confirming results of previous studies (e.g., Djath et al, 2018;Djath and Schulz-Stellenfleth, 2019;Cañadillas et al, 2020;Siedersleben et al, 2020). Consistent with the observations by Lampert et al (2020), atmospheric model simulations by Siedersleben (2019) show a reduction of wind speed by 5%-25% inside the wind wake 5 km downwind of a wind farm.…”
Section: Effects Of Wind Turbines On the Wind Fieldsupporting
confidence: 87%
“…The unique data have been the basis for different studies, proving for the first time directly the horizontal extension of wakes downwind of offshore wind parks (Platis et al, 2018), quantifying the wind speed recovery in relation to stability Platis et al, 2020) and validating the WRF mesoscale model (Siedersleben et al, 2018a(Siedersleben et al, , b, 2020, which can then be used for larger scales and future wind energy scenario calculations.…”
Section: Discussionmentioning
confidence: 99%
“…Convective processes up to the formation of thunderstorms in the atmosphere were studied by direct measurements in the clouds and drop sondes released from the aircraft (Groenemeijer et al, 2009). The aircraft was deployed above the Mediterranean to investigate cyclones and mesoscale convective systems to understand which atmospheric conditions lead to devastating thunderstorms, and to improve the forecasting of such systems Ducrocq et al, 2014;Sodemann et al, 2017). A comparison of convective boundary layer conditions between wind lidar and airborne measurements was performed (Adler et al, 2019).…”
Section: Research Aircraft Dornier 128mentioning
confidence: 99%
See 1 more Smart Citation
“…Users can adjust the specifications of the parameterized turbine, including its rotor diameter, hub height, thrust coefficients, and power curve, as well as its latitude and longitude location. WFP simulations have been validated with power production data (Lee and Lundquist, 2017a) and airborne measurements of winds (Siedersleben et al, 2018b), temperature and moisture (Siedersleben et al, 2018a), and turbulence (Siedersleben et al, 2020) and have reproduced the observed localized, nighttime, near-surface warming produced by wind turbines mixing warmer air from the nocturnal inversion down to the surface (Fitch et al, 2013;Cervarich et al, 2013;Lee and Lundquist, 2017b;Xia et al, 2017Xia et al, , 2019. To our knowledge, the WRF WFP has not yet been applied to explore interactions between wind farms and transient phenomena like thunderstorm outflow boundaries.…”
mentioning
confidence: 94%